A comparative analytic study of knowledge, attitude and practice of breast feeding in primi and multipara women at a tertiary care centre in Gujarat, India - Patel, Manthan; Prajapti, Shetal (International Journal of Research in Medical Sciences, 2016)
Background: Mother’s milk undoubtedly represents the best nourishment for the child during first months of life. The benefits of breastfeeding (BF) specially, exclusive breastfeeding (EBF), are well established. No artificial feed can replace breast milk, its specific nutrients and protection against diseases. All women should be encouraged to exclusively breastfeed their infants up to 6 months of age and thereafter to continue along with appropriate and adequate complementary foods, for up to 2 years of age. Methods: In the present study, we aimed to study and to compare knowledge, attitude and the feeding practices in a primi and multi para at tertiary care centre. The descriptive study was conducted in Obstetrics and Gynaecology Department of Government Medical College and Hospital, Rajkot, Gujarat, India. Women were interviewed personally with the help of a fixed questionnaire regarding their knowledge attitude and feeding practices. Results: In the present study, we aimed to study and to compare knowledge, attitude and the feeding practices in a primi and multi para at tertiary care centre. The descriptive study was conducted in Obstetrics and Gynaecology Department of Government Medical College and Hospital, Rajkot, Gujarat, India. Women were interviewed personally with the help of a fixed questionnaire regarding their knowledge attitude and feeding practices. Conclusions: Efforts need to be made to help mother to initiate feeding early specially in caesarean section. Women need to be made aware of benefits of breast feeding and proper techniques. Health care providers and nursing staff should be encouraged to actively participate in proper counselling and training of mothers.